Burnout and Mental Health and Well-Being of School Nurses After the First Wave of the COVID-19 Pandemic: A National Cross-Sectional Survey. (April 2023) - Chen, Hsiao-Jung; Liao, Li-Ling; Lin, Hui-Ling; Chang, Li-Chun
The aim of this study was to examine the associations between job stressors, COVID-19-related concerns, burnout, and mental health and well-being among school nurses, and whether any of these associations are mediated by burnout. Based on stratified proportional sampling, data collection was conducted by an online questionnaire distributed to 600 school nurses in Taiwan. A total of 256 participants aged between 27 and 62 years (mean = 47.08; standard deviation = 7.28) returned questionnaires. Results showed that burnout was the main mediating variable that fully mediated the relationship between COVID-19-related concerns and mental health and well-being. The effects of job stressors on mental health and well-being included direct negative effects (β = −.29) and indirect negative effects (β = −.67) through mediating factors. School health managers should be more aware of burnout and mental health and well-being among school nurses under the impact of COVID-19.